2011
DOI: 10.1159/000328805
|View full text |Cite
|
Sign up to set email alerts
|

Early Start of Chemotherapy after Resection of Primary Colon Cancer with Synchronous Multiple Liver Metastases:A Case Report

Abstract: The start of chemotherapy treatment usually requires a delay of about 4 weeks after surgical resection in patients with primary colorectal cancer and synchronous distant metastasis. However, there is no evidence to indicate the required length of this delay interval. In addition, there is a chance that a patient may die because postoperative chemotherapy was not started soon enough and a metastatic tumor was able to develop rapidly. Here, we present a case in which combination chemotherapy with capecitabine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…reported the independent prognostic value on survival of primary tumor resection in patients with CRC and unresectable metastases [13]. Other authors have suggested deferring the resection of minimally symptomatic colorectal tumors because most of these patients succumb to progressive systemic disease instead of the complications related to the intact primary lesion [8,10,14]. We reported on a case involving an early chemotherapy start in a patient who had undergone right hemicolectomy for synchronous multiple liver metastases [14].…”
Section: Resultsmentioning
confidence: 99%
“…reported the independent prognostic value on survival of primary tumor resection in patients with CRC and unresectable metastases [13]. Other authors have suggested deferring the resection of minimally symptomatic colorectal tumors because most of these patients succumb to progressive systemic disease instead of the complications related to the intact primary lesion [8,10,14]. We reported on a case involving an early chemotherapy start in a patient who had undergone right hemicolectomy for synchronous multiple liver metastases [14].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, even for patients with metastatic colorectal cancer in the IV phase, several reports proposed that early initiation of PAC could significant ameliorate the prognosis after palliative operation. Two case reports conducted by Yoshida Y. et al, [18] [19] in 2011 and 2012 had shown that stage IV colon cancer with liver metastases and brain metastases, after palliative resection of tumor associated metastasis, prescribing the first PAC within one week, not only the patients suffered from little chemotherapy induced adverse reactions, but the PFS had reached six months and four months, respectively. It was still Yoshida Y. et al, [20] [4] summarized PAC interval ā‰„ 8 weeks wouldn't impact 5-year OS or RFS.…”
Section: Discussionmentioning
confidence: 99%
“…In most clinical trials, patients who underwent an operation within 4 weeks were excluded. We reported a case involving the early initiation of chemotherapy on postoperative day 7 who had undergone right hemicolectomy for synchronous multiple liver, lung, and peritoneal metastases 26. He survived without postoperative complications for 22 months despite huge liver metastases.…”
Section: Discussionmentioning
confidence: 99%